Algorithms for Solving the Variational Inequality Problem over the Triple Hierarchical Problem. (11th June 2012) - Jitpeera, Thanyarat; Kumam, Poom
Abstract : This paper discusses the monotone variational inequality over the solution set of the variational inequality problem and the fixed point set of a nonexpansive mapping. The strong convergence theorem for the proposed algorithm to the solution is guaranteed under some suitable assumptions.